Renal pseudoaneurysm after blunt trauma in a 10-year-old girl: A case report. Issue 2 (May 2021) - Sforza, Simone; Persano, Giorgio; Cini, Chiara; Sforzi, Idanna; Grosso, Antonio Andrea; Bronzini, Francesca; Bussolin, Leonardo; Acquafresca, Manlio; Masieri, Lorenzo
Introduction: Renal trauma is a relevant cause of morbidity in children older than 1 year. Most patients are currently managed conservatively, even in case of high-grade traumas; nevertheless, harmful complications may occur even in hemodynamically stable patients. We present a case of grade IV blunt renal trauma complicated by post-traumatic pseudoaneurysm. Case description: A 10-year-old girl was referred to our institution for grade IV trauma of the right kidney. During observation she had persistent hematuria that caused anemia. A second contrast-enhanced computed tomography scan revealed a posttraumatic pseudoaneurysm that was successfully treated by angiographic embolization. Conclusions: Although extremely rare after blunt renal trauma, post-traumatic renal pseudoaneurysm may cause severe blood loss and anemia, and angioembolization is therefore indicated. This condition should be suspected and move physicians to investigate further.